ANALYSIS OF THE MORBIMORTALITY OF TRAFFIC ACCIDENTS VICTIMS: A REVIEW - Santos, Fernanda Batista Oliveira (2013)
http://dx.doi.org/10.5902/217976926206Traffic accidents are among the leading causes of death, and in Brazil, this represents the third leading cause of death, surpassed by homicides and heart diseases. Objective: to evaluate publications seekingto identify the morbidity and mortality profile of traffic accidents. Method: this review was conducted in the Virtual Health Library, using the followingdescriptors: “medical emergency” AND “traffic accident” AND “morbidity” AND “mortality”. We used the following limits: studies published from 1988 to 2010, in Portuguese and English. 47 studies have been identified. 15 articles were selected through exploratory reading. Results: in general, the head is the body area most affected, followed by lower limbs that are affected by fractures. Although indicators with different values were found, high morbidity and mortality are confirmed. Concluding remarks: the prevention of accidents may be reached through public education, to decrease the frequency of health complications and deaths.